Introducing a novel dashboard for assessing risks in potential explosive working areas based on maintenance management. - García Moreno, Richard (EASI: Engineering and Applied Sciences in Industry, 2023)
Industries handling combustible powders are subject to strict regulations and standards to prevent and control the risk of explosions. Explosive atmospheres (ATEX) are mixtures of flammable substances in the form of gas, vapor, mist, or dust in the air, which can lead to an explosion under appropriate conditions. A new dashboard is proposed to evaluate the risk of dust explosions. This tool leads the identification and classification of potential explosive environments, based on suitable technical and organizational indicators derived from a systematic literature review (PRISMA). The new control panel allows the analysis of the adherence level to safety indicators in areas classified as explosive due to dust. A new questionnaire and action plan is designed, with a safety implementation ramp. The control panel is a crucial tool in risk management by monitoring and controlling processes, guiding procedures, and promoting training and best practices in potentially explosive work environments. The goal is to raise awareness and minimize accidents and incidents related to combustible dust.
Keywords: atex; dust explosion; explosive atmospheres; combustible dusts; dashboard